Grape pomace in diets for Podolian and crossbred young bulls: effects on growth performance, meat quality, and economic analysis of meat production - Giannico, Francesco; Petrontino, Alessandro; Bozzo, Francesco; Karatosidi, Despoina; Selvaggi, Maria; Carbonara, Claudia; Tarricone, Simona; Ragni, Marco; Colonna, Maria Antonietta (Frontiers in Animal Science, 2025)
The use of local by-products in diets for beef cattle is a useful tool for circular economy; Apulia is the second Italian region for wine making that leads to the production of great amounts of grape pomace (GP), that has a high nutritional potential due to the presence of many bioactive compounds. Forty-eight male calves were used: 16 purebred Podolian, 16 Limousine × Podolian (L×P) and 16 Marchigiana × Podolian (M×P) crossbreeds. Within each genotype, two homogenous groups of eight animals were made and fed a control diet or a diet containing 20% Grape Pomace (GP). Animals were slaughtered at 600 kg. Podolian young bulls needed a longer period to reach the slaughtering weight, with significant differences as compared to the M×P (p< 0.05) and to the L×P (p< 0.01) bulls. L×P and P young bulls showed a greater GP feed consumption (p< 0.01). The carcasses from L×P young bulls were classified as U, while M×P and Podolian were scored as R. The Malondialdehyde (MDA) concentration of meat was lowered (p< 0.05) by the dietary inclusion of GP in all the genotypes. Ageing across 3, 9 and 14 days lowered the shear force in raw and cooked meat, that was greater (p< 0.05) in P bulls as compared to the other two crossbreeds; the MDA content of meat (p< 0.05) increased during storage, irrespective of the diet and genotype. The diet containing GP led to a lower (p< 0.05) concentration of palmitic acid, total Saturated Fatty Acids and total Mono Unsaturated Fatty Acids, while increasing (p< 0.01) the concentration of Linoleic acid, total Poly Unsaturated Fatty Acids, total n-6 and total CLA (p< 0.05), in all the genotypes. For the M×P crossbred bulls, the GP variation rate was negative, while it was positive for the other two genotypes, showing a range of 0.46% in Podolian young bulls to 2.00% in L×P bulls. This preliminary study confirms the usefulness of dietary inclusion of grape pomace in young bulls’ diet with benefits in terms of economic circularity, and meat production and quality.